Bond-slip in reinforced concrete elements - Luccioni, Bibiana Maria (2005)
A model for fiber reinforced composites that takes into account the fiber slipping is presented in this paper and applied to the analysis of reinforced concrete elements. The model is formulated within the framework of the plasticity theory and the mixtures theory, considering two phases corresponding to the matrix (concrete) and the fibers (reinforcing bars) and modifying the behavior of the last to take into account the relative displacement between the two phases. An elasto-plastic interface model developed by other writers is used to describe the bond-slip mechanism. The resulting model is attractive for the analysis of reinforced concrete problems at the macro-structural level since the explicit discretization of reinforcing bars and interface is not required, with the consequent computational cost reduction. The paper concludes with application examples and comparisons with experimental results of reinforced concrete elements that show the capacity of the model developed. © ASCE.